The TRIPLE Change Framework: Merging Theories of Intersectional Power, Learning, and Change to Enable Just, Equitable, Diverse, and Inclusive Engineering Education - Vanessa Svihla; Susannah C. Davis; Nadia N. Kellam (Studies in Engineering Education, 2023)
Background: Despite many calls for change, and especially change aligned to diversity, equity, inclusion, and justice (DEIJ) goals, engineering continues to show disparities in the opportunities, experiences, and outcomes of women and people from groups historically marginalized in these fields. In response, institutions have traditionally used change frameworks to both understand and create reform at program, department, or college levels. However, when aiming at DEIJ goals, change frameworks alone do not lead to the desired transformations of systems. Purpose: In this theoretical paper, we develop an integrated framework that draws from three theoretical domains to guide systemic, equity-focused transformation in engineering education. We argue knowledge from three domains—intersectional power, learning, and change—is necessary to account for and address the complexity of DEIJ change projects. This complexity requires a framework that sheds light on interrelated embodiments of power relations, guidance on how to change, including how and why people learn and engage in new practices. Scope: To illustrate the need for and value of such integration, we examine how prior researchers have used theories of power, change, and learning. In doing so, we present a framework for how integration across these domains can occur. In the domain of change, we identified papers on diffusion of innovations and communities of practice. In learning, we identified papers on distributed practice and legitimate peripheral participation. We examined how these papers utilized critical theories of intersectional power, the third domain, in tandem with these theories. We also explored how the choice of a theory (within the domains) can help or hinder the attainment of systematic, equity-focused transformation. Discussion/Conclusion: We drew the three domains together to consider how these, when integrated in the Theories and Research on Intersectional Power, Learning, and Evolutionary Change (TRIPLE Change) Framework, provide a more comprehensive means to envision, guide, and characterize DEIJ change efforts. By integrating learning, change, and intersectional power theories, we increase the capacity of our analyses of systems and open new possibilities for creating more equitable and just systems.